PENGARUH PEMAHAMAN PENGETAHUAN PAJAK, KUALITAS PELAYANAN, SANKSI PAJAK DAN KESADARAN WAJIB PAJAK TERHADAP KEPATUHAN MEMBAYAR PAJAK UMKM DI SEMARANG (Studi Empiris Pada Wajib Pajak Badan Yang Terdaftar Di KPP Pratama Dan KPP Madya Di Semarang) - Nur Laila Hasna, 12.05.52.0062; Jaeni, Jaeni (Students Journal of Accounting and Banking, 2016)
This study aims to examine and analyze the effect of Understanding tax knowledge, Quality of Service, tax penalties, and Consciousness Taxpayer, to compliance of SMEs registered to pay tax on STO and KPP Madya Semarang either partially or simultaneously. The study population is the entire tax professionals who work in the company SME in Semarang, while the sample population is eligible study of 124 respondents. The process of collecting data from respondents was conducted by distributing questionnaires to 130 taxpayer with incidental sampling technique. Test instruments used are validity and reliability. Test requirements analysis using normality test, multicollinearity, heteroscedasticity test and autocorrelation. Data were tested using multiple linear regression, the determinant test, F test (Goodness of Fit), and hypothesis testing using T test.Keywords: Understanding Of Tax Knowledge, Quality Of Service, Tax Penalties, A Taxpayer Awareness, Adherence To Pay Taxes